Penyusunan dan Publikasi Karya Ilmiah: Bimtek terhadap Guru-Guru di Wilayah Perbatasan NKRI-Timor Leste - Aloisius Loka Son; Oktovianus Mamoh; Maria Rosalinda Talan; Dominikus Nitsae (Jurnal Pengabdian Sains dan Humaniora, 2023)
Writing and carrying out the process of publishing scientific papers for teachers is not an easy job. Therefore, this community service activity is carried out to equip teachers with an understanding of the systematics of an article, tricks for finding quality references, the use of grammar in writing scientific papers, strategies to avoid plagiarism traps, the style of journal templates, and the process of submitting articles. The methods of this community service are lectures and discussions. This activity was carried out online for 3 days, with 163 participants. Through the methods of activity above, participants can add insight into writing and submitting scientific articles, but participants have not yet produced scientific articles. Therefore, it is recommended that similar activities in the next period focus more on assisting participants to write articles, as well as assisting in the submission process and revision to the publication of articles in journals.